An American perspective on equal educational opportunities - Russo, C; Perkins, B (Perspectives in Education, 2004)
The United States Supreme Court ushered in a new era in American history on May 17, 1954 in its monumental ruling in Brown v Board of Education, Topeka, Kansas. Brown is not only the Court's most significant decision on race and equal educational opportunities, but also ranks among the most important cases it has ever decided. In Brown a unanimous Court struck down the pernicious doctrine of “separate but equal” in holding that the de jure segregation of students in public schools on the basis of race deprived minority children of equal educational opportunities in violation of the Equal Protection Clause of the Fourteenth Amendment. In addition to its impact on school desegregation, Brown has been the catalyst for revolutionary change influencing just about every facet of American society. Given the breadth of changes that it spawned, this article briefly reviews the Supreme Court's ruling in Brown before turning to the two most important educational areas where it has been the key, namely special education and sexual harassment.
tex.unique-id: ISI:000223927200004
Keywords: dept.eng; ⛔ No DOI found